Integrating Copyright in the Curriculum: A Study of LIS Courses of Central Universities of India - Thapa, Neelam (Journal of Copyright in Education & Librarianship, 2019)
This research aims to study the library and information science (LIS) curriculum presently followed in the central universities of India to identify the ways in which it incorporates copyright information. The central universities offering LIS programs were identified and the curricula and syllabi of these LIS programs were downloaded from the universities’ official websites. A detailed content analysis of the curricula and syllabi shows that there is no uniformity in the names of the courses taught and the course content in LIS programs of different universities. However, copyright has been included in the curriculum as part of a course in most of the universities. Based on the analysis suggestions have been made for the inclusion of copyright concepts in the curricula of LIS programs.